Pasto and modernizing attempts in the period of the Liberal republic (1930-1946) (2012)
This paper discusses two aspects of the history of related  Pasto attempts to modernize the urban environment and the communication and integration with the rest of the country and abroad. The social imaginary focused on  progress, driven by liberal team in government, managed to mobilize the people of the region around two objectives, mobility through the installation of railway Nariño and improved living conditions urban, to celebrate the centennial of the city.